Measuring Self on Social Media: Adapting the Facebook User Self Presentation Instrument - Alvani, Gemelly; Setiyowati, Ninik; Pambudi, Kukuh Setyo; Tania, Basma; binti Nor Azmi, Aimie Amiera Azureen (Ilomata International Journal of Social Science, 2025)
Self-presentation is conveying or communicating information about an individual, how they perceive something, and how individuals can influence the feelings of others who have about themselves. Self-presentation carried out by individuals presents themselves differently from the authentic self, including the authentic self, the ideal self, and the false self in social media interaction. This study aims to test the validity of the Self-Presentation instrument on Facebook users. This instrument measures how Facebook users present themselves on the platform. A total of 324 Facebook users participated in this study. Data were collected through an online questionnaire. The analysis showed that the Self-Presentation instrument's initial measurement model did not meet the fit criteria. Therefore, modifications were made by eliminating items with low factor loadings and high residual variance. After modification, the measurement model of the Self-Presentation instrument showed a good fit with a GFI value of 0.993, RMSEA of 0.088, CFI of 0.973, and TLI 0.949.